The identification of circular RNAs from peripheral blood mononuclear cells in systemic lupus erythematosus - Fengping Zheng; Xiangqi Yu; Donge Tang; Xiaoping Hong; Xinzhou Zhang; Dongzhou Liu; Yong Dai (BMC, 2021)
Abstract Background The diagnosis of systemic lupus erythematosus (SLE) is complicated. This study explores the expression of circular RNAs (circRNAs), which are closed non-coding RNAs in which the 5' and 3' ends are covalently linked and which work by sponging microRNAs. CircRNAs were extracted from peripheral blood mononuclear cells (PBMCs) of SLE patients to identify novel circRNA species that might be used for SLE diagnosis. Methods Microarray was applied to screening circRNAs changes in PBMCs obtained from SLE patients (n = 10) and healthy participants (n = 10), paired for age and sex. We then verified the selected circRNAs in PBMCs using quantitative reverse transcription-polymerase chain reaction amplification (qRT-PCR) in another cohort, including ten paired SLE patients and healthy participants. The correlation between the differential circRNAs and clinical pathology of SLE were analyzed. Results 182 up-regulated and 563 significantly down-regulated circRNAs in PBMCs of patients with SLE were identified. Besides, the qRT-PCR results were consistent with the microarray results. The correlation analysis revealed that has_circRNA_100236, has_circRNA_102489, and has_circRNA_101413 were correlated with positive anti-dsDNA, thrombocytopenia, and positive IgG, respectively. Lastly, their miRNAs targets and the binding sites were predicted. Conclusion We identified some dysregulated circRNAs in PBMCs from SLE patients, and these circRNAs may be developed as the novel biomarkers for the diagnosis of SLE.